7.9k views
1 vote
Find the inverse of the given function f(x) =2^x+6

User Meredrica
by
4.4k points

1 Answer

3 votes

Answer:


f^(-1)(x) = log_2(x-6)

Explanation:

To find the inverse
f^(-1)(x) of a function follow the following steps.

1) Do y = f (x)


f(x) =y= 2 ^ x + 6


y= 2 ^ x + 6

2) Solve the equation for the variable x.


y= 2 ^ x + 6\\\\y-6 = 2^x\\\\log_2(y-6) = x\\\\x=log_2(y-6)

3) exchange the variable y with the variable x


x=log_2(y-6)\\\\y=log_2(x-6)

Finally the inverse is:


f^(-1)(x) = log_2(x-6)

User Peirix
by
5.8k points